The Role of Religious Courts in the Application of Islamic Law in the Field of Sharia Pawnbroking - Revalina Putriyana Faza; Wahyu Nur Hidayah; Royyan Ulya Safiinatun Najah; Sofia Nuraini; Mohammad Omar Hanif; Mohammad Fanny Amrullah; Albryan Wahyu Putra Sejati; Naufal Farid Giovani; Abdullah Tri Wahyudi (Indo Publishing, 2026)
This study aims to analyse the role of the Religious Court in the application of Islamic law in the field of Islamic pawnbroking. Islamic pawnbroking (rahn) serves as an alternative to the conventional pawnbroking system, free from usury and based on the principles of justice, transparency and mutual assistance. In practice, Islamic pawnbroking utilises various contracts such as rahn, ijarah, qard, mudharabah, and bai’ muqayyadah, tailored to the needs of the customers. This study employs a normative legal research method using a literature review (library research) approach, through an examination of legislation, DSN-MUI fatwas, the Compilation of Sharia Economic Law (KHES), academic journals, and literature relevant to the sharia economy and the jurisdiction of the Religious Courts. In line with the expansion of the Religious Courts’ jurisdiction under Law No. 3 of 2006, Islamic economic disputes, including Islamic pawnbroking, have become the exclusive jurisdiction of these courts. The research findings indicate that the Religious Courts not only act as dispute resolvers but also provide legal reinforcement, legal certainty, and judicial oversight over Islamic pawnbroking practices. The existence of the Religious Courts has led to increased public trust, institutional professionalism, and the institutionalisation of Islamic economic law within the national legal system. Furthermore, these powers have helped to promote the standardisation of contractual practices and institutional compliance with Sharia principles. However, challenges remain in the form of limited human resource capabilities and low levels of legal literacy regarding Islamic economics among the public.